P0063CLINICAL CHARACTERISTICS OF PATIENTS WITH GENETICALLY CONFIRMED ALPORT SYNDROME. (6th June 2020) - Ozdemir, Gulsah; Gulhan, Bora; Atayar, Emine; Canpolat, Nur; Soylemezoglu, Oguz; Ozcakar, Z Birsin; Kara Eroğlu, Fehime; Candan, Cengiz; Kasap Demir, Belde; Soylu, Alper; Yuksel, Selcuk; Alpay, Harika; et al.
Abstract: Background and Aims: Alport syndrome (AS) is an inherited glomerular basement membrane disease caused by mutations in COL4A3, COL4A4 or COL4A5 genes. Recently, it has been reported that focal segmental glomerulosclerosis (FSGS) can be seen in AS and COL4A mutations can be detected in FSGS. In this study, we aimed to define the clinical characteristics of patients with genetically confirmed AS, in order to establish genotype-phenotype correlation and investigate the effects of different treatment regimes. Method: A total of 87 pediatric AS patients included in this multicenter study. We retrospectively collected data from medical records and requested other centers to fill out a questionnaire, which included data regarding patient demographic features, family history, clinical and laboratory characteristics at first presentation, histopathological (if available) and genetic tests results, treatments and yearly follow-up results. Results: A total of 87 (41 female, 46 male) genetically confirmed AS patients ( COL4A5, n=43; COL4A3, n=25; COL4A4, n=19) were studied. Mean age at first presentation was 7.6±4.1 years and the median follow-up duration was 4.3 years (IQR 1.9–7.3). 14 (16.1%) of 87 patients presented with nephrotic syndrome (NS); renal biopsy findings showed FSGS in 11 (79%) of 14 patients with NS, and COL4A3 mutations were the most common (n=7, 50%) in this group. Of 14 NS patients, 12 received steroid, 11 received cyclosporine (CsA) and 4 received other immunosuppressives prior to genetic diagnosis. The inheritance pattern of the patients with NS was consistent with ARAS in 10 patients (71.4%), XLAS in 3 patients (21.4%), and ADAS in 1 patient (7.2%). During follow up, glomerular filtration rate (GFR) decreased below 90 ml/min/1.73 m 2 in 24 of 87 patients (27.5%). COL4A3 mutations (n=14, 58.3%) were the leading genetic abnormality in patients who progressed to chronic kidney disease (CKD). At the last visit, GFR loss was significantly higher in patients with COL4A3 mutations when compared to patients with COL4A4 and COL4A5 mutations (p=0.04). Among patients with NS, 9 of 14 (64.2%) progressed to CKD. Genetic results of patients with NS who progressed to CKD were COL4A3 in 6 (66.7%), COL4A4 in 2 (22.2%) and COL4A5 in 1 (11.1%) patients. In survival analysis, renal survival rate without CKD was 12.1 years (95% CI: 6.7-17.5). After the first presentation, the 5-year cumulative risk of CKD was 51.8%, 12.6%, and 12.9% in patients with COL4A3, COL4A4 and COL4A5 mutations, respectively (p=0.001). We observed that patients with COL4A3 mutations, ARAS inheritance pattern, histopathology of FSGS or NS presentation progressed to CKD earlier (p<0.001 for COL4A3, p=0.01 for ARAS, p=<0.001 for FSGS, p=0.01 for NS presentation) when compared to those without. CsA treatment did not improve renal survival. Conclusion: Detailed analyses of data from genetically confirmed Turkish patients with AS provided important clues regarding to the presentation, course and outcomes of the disease. COL4A3 mutations, ARAS inheritance pattern, NS presentation and FSGS finding in renal biopsy are major risk factors for progression to CKD. We recommend genetic testing for patients suspected of having AS. Furthermore, COL4A mutations should be considered in patients with FSGS and steroid resistant NS. This approach will shed light on the prognosis of patients and help with definitive diagnosis, preventing unnecessary and potentially harmful medications.